T cells regulation modulated by Sambucus javanica extracts in DMBA-exposed mice - Wira Eka Putra; A. Rofiqi Maulana; Arfan Tri Kusuma Ramadhan; Muhaimin Rifa’i (Journal of HerbMed Pharmacology, 2020)
Introduction: Sambucus is a genus of the Adoxaceae family and has been widely used as a food and medicinal source. In this study, we aimed to evaluate the effects of S. javanica extracts toward T cells regulation in the 7,12-dimethylbenzene (a) anthracene (DMBA)-exposed mice. Methods: Thirty mice were used in this experiment which divided into six treatment groups and five times repetition. Three-month-old BALB/c mice were administrated with 2.8 mg.kg-1 BW of DMBA as carcinogen agent for ten times within four weeks, then continuously treated with 400 and 800 mg.kg-1 BW of S. javanica berries leaves extracts daily for two weeks. Treatment groups in this study were vehicle as negative control, DMBA 2.8 mg.kg-1 BW as positive control; BD1 group, DMBA 2.8 mg.kg-1 + berries extracts 400 mg.kg-1 BW; BD2 group, DMBA 2.8 mg.kg-1 + berries extracts 800 mg.kg-1 BW; LD1 group, DMBA 2.8 mg.kg-1 + leaves extract 400 mg.kg1 BW; and LD2 group, DMBA 2.8 mg.kg-1 + leaves extract 800 mg.kg-1 BW. The relative number of CD4+CD25+CD62L+ cells and CD4+CD62L+ cells were measured and analyzed by using flow cytometer. Results: DMBA induction decreased the relative number of CD4+CD25+CD62L+ cells while the leaves extract of S. javanica significantly increased their expression. Furthermore, DMBA promoted the relative number of CD4+CD62L+ cells expression while leaves and berries extracts of S. javanica sharply suppressed its expression. Conclusion: The results suggest that, S. javanica extracts may exert their medicinal properties by modulating T cells regulation in DMBA-induced mice.